Gigi Tiruan Sebagian Lepasan Kerangka Logam dengan Desain Swing Lock sebagai Perawatan Splint Periodontal - Andi Adytha MIR; Heri Siswanto; Dharma Satya Aprianto; Chaerita (E-Prodenta Journal of Dentistry, 2023)
Providing the best denture treatment for patients with tooth mobility is quite challenging and requires a collaboration between the prosthodontist and periodontist. This study aims to describe the use of a metal frame removable partial denture with a swing lock as a suitable treatment option for individuals who suffer periodontal disease-related with tooth mobility. The case is a 55-year-old male patient complained of mobility and several diastemas in his lower front teeth. The patient claimed to regularly visit an internist for checks despite having diabetes mellitus. The patient asked to get his teeth fixed. He wanted to properly chew his food while wearing the denture. Treatments for the patient included DHE, scaling, and root planing. A bone transplant and periodontal flap operation were subsequently planned for the patient the following week. A metal-frame partial denture with a swing lock will be the patient's final treatment. Metal frame partial denture is one of the treatment options as a periodontal splint to treat the tooth with mobility. Metal frame partial denture with swing lock is an alternative treatment for conditions related to periodontal disease that require optimum stabilization.